2016
DOI: 10.1186/s12977-016-0302-9
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon responses are impaired in latently HIV infected cells

Abstract: Background The latent HIV-1 reservoir represents the primary barrier to the eradication of HIV-1 infection. The design of novel reservoir-clearance strategies, however, is impeded in part by the inability to distinguish latently HIV-infected cells from uninfected cells. Significant impairment of the type I interferon (IFN-I) response is observed during productive HIV-1 infection. Although this remains poorly described in the context of latent HIV-1 infection, presence of potential defects may serve as a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…26 In vitro studies also support this model, as widespread defects in IFN-I responsiveness are observed within latently HIVinfected cell lines. 27 Thus, latency may be established early after transmission to avoid an IFN-mediated inflammatory response, allowing the virus to surreptitiously traffic away from the mucosa and migrate into the lymphoid tissues, where IFN resistance promotes viral replication, while creating a target-rich environment in which the virus can spread.…”
Section: Seeding the Latent Hiv Reservoir In The Mucosamentioning
confidence: 99%
“…26 In vitro studies also support this model, as widespread defects in IFN-I responsiveness are observed within latently HIVinfected cell lines. 27 Thus, latency may be established early after transmission to avoid an IFN-mediated inflammatory response, allowing the virus to surreptitiously traffic away from the mucosa and migrate into the lymphoid tissues, where IFN resistance promotes viral replication, while creating a target-rich environment in which the virus can spread.…”
Section: Seeding the Latent Hiv Reservoir In The Mucosamentioning
confidence: 99%
“…Unfortunately, this response is usually ineffective to suppress HIV-1 activity, due to the ability of this virus to hijack host immune system and evade the IFN-mediated antiviral activities ( 4 ). Moreover, the persistent IFN-I secretion greatly disturbs the immune homeostasis, contributing to immune activation-dependent disease progression ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…These models are characterized by extremely low frequencies of cells latently infected with HIV-1, making them poorly suited for investigating biological mechanisms of reactivation and killing. As such, cell line models have been used to investigate important differences between cells latently infected with HIV-1 and cells that are uninfected, including activation of cell death pathways upon stimulation [ 8 ] and impairment of antiviral responses mediated by type I interferon (IFN-I) [ 9 ].…”
mentioning
confidence: 99%
“…HIV-1 has evolved countermeasures to escape IFN-I–mediated immune control during productive infection, including degradation of pattern-recognition receptors [ 10 , 11 ], inhibition of IFN regulatory factors [ 12 ], and impairment of antiretroviral restriction factors [ 13 , 14 ]. While the ability to investigate IFN-I signaling defects during latent infection of primary cells remains a challenge, we have recently demonstrated that the induction of various IFN-stimulated genes following IFN-α or polyinosinic:polycytidylic acid stimulation is impaired in cell lines latently infected with HIV-1 [ 9 ]. Impaired IFN-I signaling in cell lines latently infected with HIV-1 may therefore represent a target for the design of therapeutic strategies intended to eliminate major HIV-1 reservoirs.…”
mentioning
confidence: 99%